Development of a competency for professional oral hygiene care of endotracheally-intubated patients in the intensive care unit: development and validity evidence - Eun-Sil Choi; Hie-Jin Noh; Won-Gyun Chung; So-Jung Mun (BMC, 2021)
Abstract Background Professional oral care in the intensive care unit may reduce the incidence of Ventilator Associated Pneumonia, which increases the patient's mortality rate. This study aimed to develop a competency for professional oral hygiene care of endotracheally-intubated intensive-care patients. Methods First, we developed a competency draft by reviewing the literature on oral hygiene care of patients in the intensive care unit. Next, we developed expert validity test questionnaires using this draft and conducted expert validity tests twice on 18 experts. We determined competency as a content validity index of 0.8 or more and received expert additive opinions about competency through an open-questionnaire expert validity test paper in this methodology study. Results The content validity index ranged from 0.8 ~ 1.0 for all items. The competency of 'professionalism' comprised 2 sub-competencies with 7 behavioral indicators. 'POHC preparation' comprised 3 sub-competencies with 10 behavioral indicators. 'POHC implementation' comprised 3 sub-competencies with 6 behavioral indicators. 'POHC evaluation' comprised 2 sub-competencies with 8 behavioral indicators. Lastly 'Cooperation among experts' comprised 3 sub-competencies with 7 behavioral indicatiors. Conclusions To provide patients with high quality oral hygiene care, these competencies should be implemented, and oral hygiene care professionals and related medical personnel should form a cooperative system.